Konsep Al-Qur'an Dalam Gagasan Moderasi Beragama: Menyelaraskan Akhlak Dan Keyakinan - Arifin, Muhammad (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2025)
The Qur'an, the holy book of Muslims, contains content that is timeless and universally applicable (masalih li> kulli> zama>n wa maka>n). One of the important concepts in the Qur'an is the idea of religious moderation. Religious moderation is a principle that advocates the importance of maintaining balance, justice and moderation in all aspects of worldly life. It emphasises the importance of being moderate in terms of belief, worship and ethical behaviour. The Qur'an consistently portrays the idea of religious moderation in a comprehensive framework that encompasses a variety of character traits, such as honesty, open-mindedness, love, and flexibility. These traits are interconnected, holistic and universal, reinforcing each other and offering collective benefits. This research also aims to identify the main values underlying the idea of religious moderation and how they can be applied in daily life to create balance, justice and harmony. This research uses a qualitative approach with thematic interpretation (mawdu'i) analysis method. The main data used are the verses of the Qur'an related to religious moderation, supported by classical and contemporary interpretations to enrich the analysis. The results show that the Qur'an offers a clear and comprehensive framework regarding religious moderation. This idea includes a number of main characters such as honesty, open-mindedness, love, and tolerance.